Conference Report: Applied Pharmaceutical Analysis India 2013 Conference Report. (August 2013) - Kole, Prashant; Shedbalkar, Vinay; Raina, Vijay; Subramanian, Murali; Barot, Deepak; Mandlekar, Sandhya
Applied Pharmaceutical Analysis – India, founded by The Boston Society in 2009, is a nonprofit organization that provides a unique platform to researchers in the field of drug discovery and development with specific focus on biotransformation, discovery & regulatory bioanalysis areas. It has been organizing international meetings in India since 2010, and since its inception these meetings have become an important annual event in the Indian pharmaceutical conference calendar. The fourth annual meeting for the year 2013 was held at the Hyderabad International Convention Center, Novotel, Hyderabad, India from 3–6 March. This conference report summarizes an overview of the meeting that was themed as 'Bioanalysis and biotransformation in advancing drug discovery and development: fundamentals to state of the art'. The event consisted of 1 day of short courses (parallel sessions on discovery bioanalysis and biotransformation) followed by 3 days of workshops (regulated bioanalysis, discovery bioanalysis and biotransformation). The meet was well attended by over 185 delegates and was bestowed with presentations by renowned scientists from India, China, Europe and the USA. This annual Applied Pharmaceutical Analysis meet was a unique opportunity for the organizers and participants to extend their national and international professional network, and align with recent developments in pharmaceutical analysis, discovery/development sciences and regulatory challenges. It also helped establish a global community of practice within India in analytical sciences and allied fields.